2017
DOI: 10.4306/pi.2017.14.5.618
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depression among Patients with the Top Ten Most Common Cancers in South Korea

Abstract: ObjectiveAmong the various psychiatric disorders, depression is a common comorbid condition in cancer patients. Due to the distinct and diverse nature of cancer, the prevalence of depression may be assumed to be affected by differences in primary cancer sites. In this study, we explored the prevalence rates of depression among the ten most prevalent cancers in South Korea using a national patient sample.MethodsThis was a 1-year cross-sectional study using a national patient sample provided by the South Korean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 40 publications
3
38
4
2
Order By: Relevance
“…To our knowledge, no other study has reported the combined prevalence of clinically diagnosed stress-related disorders among patients with cervical cancer. A previous study from South Korea used administrative databases to ascertain the diagnosis of depression among patients with cervical cancer and reported a prevalence of 7.9% (44). The slightly lower prevalence of depression in this study (4.9%) is likely because only clinical diagnoses made by specialists or during in-patient care were included in our study.…”
Section: Discussionmentioning
confidence: 78%
“…To our knowledge, no other study has reported the combined prevalence of clinically diagnosed stress-related disorders among patients with cervical cancer. A previous study from South Korea used administrative databases to ascertain the diagnosis of depression among patients with cervical cancer and reported a prevalence of 7.9% (44). The slightly lower prevalence of depression in this study (4.9%) is likely because only clinical diagnoses made by specialists or during in-patient care were included in our study.…”
Section: Discussionmentioning
confidence: 78%
“…Depression can also affect fatigue symptoms; 25 in fact, 5.6% to 24.0% of cancer patients suffer from depression. [26][27][28] Therefore, the concept of primary insomnia may not be fit for cancer patients, and depressive symptoms should be considered as a common comorbidity of insomnia. In this study, 63 (65.6%) patients were diagnosed as having insomnia, and 21 (21.9%) patients had major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, depressive disorder is significantly more prevalent in the lung cancer group than in the control group in our study. In a cross-sectional study using a national patient sample provided by the South Korean NHI, they found patients with lung cancer were the most prone to experience depression among the 10 most prev-alent cancers in South Korea [46]. Higher levels of psychological distress, health-related stigma, and poorer quality of life were reported in lung cancer patients than in other types of cancers [47,48].…”
Section: Prevalence Of Depressive Disordermentioning
confidence: 99%